Analisis Kesulitan Siswa Memahami Soal Numerasi Matematika Kelas V SD - Apiyudin, Apiyudin; Khatimah, Husnul (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
The objective of this research is to identify the challenges students face in understanding numeracy learning difficulties in fifth-grade mathematics. The method used is descriptive qualitative with 11 students from grade V as participants 11 Blangpidie and research sources of 1 teacher of fifth-grade students at Elementary School 11 Blangpidie participated using evaluation tools interviews, documentation, along with observations. The findings showed learners had trouble completing task numeracy problems in the form of story problems at Elementary School 11 Blangpidie. Students' difficulties when solving story problems were caused by difficulty in interpreting the meaning of the story problems, difficulty in solving problems, and difficulty in calculating. There are several efforts that teachers make to overcome these difficulties, including making the learning atmosphere more interesting and using more teaching media so that students can understand more easily and are motivated to learn